2019
DOI: 10.1186/s13223-019-0343-4
|View full text |Cite
|
Sign up to set email alerts
|

Stability of peripheral blood immune markers in patients with asthma

Abstract: Background Asthma is a complex disease with variable course. Efforts to identify biomarkers to predict asthma severity, the course of disease and response to treatment have not been very successful so far. We have previous suggested that PAR-2 and CRTh2 expression on specific peripheral blood cell subtypes may be biomarkers of asthma severity. We reasoned that parameters that remain stable when asthma symptoms are controlled would be the most appropriate to evaluate for their utility to predict lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 34 publications
0
9
2
Order By: Relevance
“…Our study shows that the number of Th2 cells (CD4 + CRTh2 + T cells) in peripheral blood during an asthma exacerbation correlates with asthma control and asthma quality of life measures, but not with pulmonary function parameters. This finding is in contrast to our previous report in a population of stable asthmatics that showed the number of Th2 cells in peripheral blood did not correlate with ACQ6 scores 20 . It is possible to speculate that the increased numbers of Th2 cells and possibly their activation status during an asthma exacerbation affect asthma control and subsequently quality of life in these subjects; especially if a previously reported 24 pathogenic phenotype of Th2 cells is overrepresented in patients during acute asthma exacerbations.…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…Our study shows that the number of Th2 cells (CD4 + CRTh2 + T cells) in peripheral blood during an asthma exacerbation correlates with asthma control and asthma quality of life measures, but not with pulmonary function parameters. This finding is in contrast to our previous report in a population of stable asthmatics that showed the number of Th2 cells in peripheral blood did not correlate with ACQ6 scores 20 . It is possible to speculate that the increased numbers of Th2 cells and possibly their activation status during an asthma exacerbation affect asthma control and subsequently quality of life in these subjects; especially if a previously reported 24 pathogenic phenotype of Th2 cells is overrepresented in patients during acute asthma exacerbations.…”
Section: Discussioncontrasting
confidence: 94%
“…To study whether immune parameters during acute asthma exacerbations are different than during the stable phase of the disease, we compared data from the ED visits with those from a cohort of stable asthmatics we reported previously 20 ; all values used for comparison were taken from the fourth visit of the previous study.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, mast cell-derived PGD 2 activated type-2 CD8 (+) T cells via the CRTH2 receptor, inducing migration and cytokine (IL-5 and IL-13) production in severe eosinophilic asthma [64]. Studies supporting these findings have shown that a larger population of CRTH2 (+) T cells was identified from the peripheral blood of patients with severe asthma, and allergen-specific Th2 cells could be identified by stable co-expression of CRTH2 [65][66][67]. PGE 2 has been proposed to induce Th2 responses by attenuating the production of IL-2 and IFN-γ by Th1 cells without enhancing the release of IL-4 by Th2 cells [26,68].…”
Section: T Cellsmentioning
confidence: 90%
“…Elevated eosinophil numbers are considered major biomarkers of asthma [22]. Eosinophilia during asthma development is associated with pro-inflammatory cytokines such as IL-4, IL-5 and IL-13 [23,24].…”
Section: Discussionmentioning
confidence: 99%